If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2(3) = 6 Multiply 2 * 3 2x + 6 = 6 Reorder the terms: 6 + 2x = 6 Add '-6' to each side of the equation. 6 + -6 + 2x = 6 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 6 + -6 2x = 6 + -6 Combine like terms: 6 + -6 = 0 2x = 0 Solving 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. x = 0 Simplifying x = 0
| 0.49=(ln)(y) | | 5(4x-9)=95 | | 7(3-1y)+2y=6 | | 0.49=ln(y) | | X^2+3x+5=y | | -2p+20=14 | | -5(4b+1)+(21b-4)=0 | | 2n^3+2n^2+2n=n*14 | | 4x-6x+1x-2=4 | | (8v-3)(3v+7)=0 | | 5w-17=28 | | 3m*2+2m=102 | | 10x-2(1)=2 | | 20-2a+4a+4a+7=48 | | 5x+-4=8+2x | | (4x+2)-(3x-6)= | | -5(.2+.2y)=-2 | | -8(5+b)-1=-89 | | 124=7x+3(x+8) | | 2(x+8)=9x-6 | | 6x-2y=48 | | (2+x)(x-3)=24 | | 5xn-3=12 | | 7x-22=6x-22 | | 10x-2y=2 | | 20-4a+4a+4a+7=48 | | -6(1+8k)=-102 | | 9.6=1.6 | | 6b+4=12 | | 8y-3y=75 | | (7y+6)-(5+6y)=5 | | (3)(2x)(x)=36 |